2011
DOI: 10.1111/j.1432-2277.2011.01286.x
|View full text |Cite
|
Sign up to set email alerts
|

Donor and recipient HLA/KIR genotypes do not predict liver transplantation outcome

Abstract: Summary Whether or not Natural Killer (NK) cells affect the immune response to solid organ allografts is still controversial. Main determinants of NK‐cell activation are specific HLA/killer‐cell immunoglobulin‐like receptors (KIR) interactions that, in transplantation, may induce NK‐cell alloreactivity. So far, in liver transplantation (LTX) donor‐versus‐recipient alloreactivity has not been investigated; in addition, studies of predicted recipient‐versus‐donor NK‐cell alloreactivity have led to contradicting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 64 publications
2
10
0
Order By: Relevance
“…Our results support the previous studies suggesting that the KIR2DL1/S1+ allogeneic T cell subset, which is specific for donor C2 ligands, may be induced, or the binding of aKIR (KIR2DS1) to a donor HLA-C2 ligand can induce alloreactivity [2122]. However, other studies demonstrated controversial data showing no impact of donor HLA-C2 genotype on graft or patient survival [91419]. HLA-C proteins may act as alloantigens, which can induce T cell activation and may also function as ligands for KIRs, modulating NK and T cell cytotoxicity [9].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our results support the previous studies suggesting that the KIR2DL1/S1+ allogeneic T cell subset, which is specific for donor C2 ligands, may be induced, or the binding of aKIR (KIR2DS1) to a donor HLA-C2 ligand can induce alloreactivity [2122]. However, other studies demonstrated controversial data showing no impact of donor HLA-C2 genotype on graft or patient survival [91419]. HLA-C proteins may act as alloantigens, which can induce T cell activation and may also function as ligands for KIRs, modulating NK and T cell cytotoxicity [9].…”
Section: Discussionsupporting
confidence: 89%
“…The ethnic differences between the previous study and our data appeared to be due to the underlying cause of LT and the type of donor. In Korea, the predominant disease necessitating LT is hepatitis B virus (HBV)-related liver disease, but in Western countries, hepatitis C virus (HCV)-related liver disease and autoimmunity account for a considerable proportion along with viral hepatitis [1119]. Although direct influence of the underlying disease on clinical outcome was not sufficient, different underlying diseases may affect patient NK cell function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study of 100 transplants showed that matching of the main HLA ligand recognised by NK cells, HLA-C, between donor and recipient, reduced the likelihood of acute rejection, with recipients who expressed no HLA-C group 2 alleles further protected from acute rejection [131]. However, later, larger studies were unable to replicate these results [132,133]. A study of HLA-C effect on chronic rejection of 595 liver transplants showed that the presence of at least one HLA-C group 2 allele in the donor was protective [132], but again this finding could not be replicated in a later study [133].…”
Section: Nk Cells In Liver Transplantationmentioning
confidence: 99%
“…However, studies of KIR-HLA class I mismatch have not conclusively correlated with graft rejection or survival. The value of HLA-C-KIR typing in predicting recipientversus-donor and donor-versus-recipient reactions has been investigated in a cohort of 348 LT patients (38). Using predictive models of NK cell alloreactivity, no correlation between HLA-C-KIR mismatch and liver transplant outcome was found.…”
Section: Nk Cells In Rejectionmentioning
confidence: 99%